Space Lexicalization in English Language Education Students’ Narrative Writing - Naima Khairunisa; Yazid Basthomi; Mirjam Anugerahwati (Journal of English Language Teaching and Linguistics, 2022)
This article discusses how Indonesian English Language Education Students (ELES) apply space lexicalization in narrative composition. This study also discusses how they understand the concept of space lexicalization. Fifteen master’s degree students in English Language Education are the subjects of this study. A convergent parallel mixed-method research design was utilized in this study. The data of this study are a set of tests on space lexicalization and a writing test. The test on space lexicalization is used to investigate the participants’ understanding of space lexicalization’s concept, while the writing test is utilized to investigate how they apply space lexicalization in narrative writing. The results show that the subjects understand the concept of space lexicalization and they can apply space lexicalization in narrative writing. This shows that Indonesian ELES has acquired space lexicalization in narrative writing, although some of them produce grammatical mistakes and incorrect combinations of spatial words.